88 D-DIMER ASSAY, A POSSIBLE TOOL IN THE EVALUATION OF ATRIAL THROMBOSIS. (1st January 2005) - Ibebuogu, U. N.; Robinson, V. J.B.; Salah., A.
Abstract : Atrial fibrillation is a common condition encountered in the cardiology inpatient service. It is associated with atrial thrombosis, which requires exclusion using transesophageal echocardiogram (TEE) before planned cardioversion. TEE can be operator dependent with a reported sensitivity of 93-100 %. 1 A significantly elevated D-dimer can help the TEE operator to look for intra-atrial clots more carefully in the absence of any other cause for an elevated D-dimer. This ultimately will increase operator efficiency. A 56 year old white male, status post renal transplant and CABG for 3 vessel CAD and a prior history of MRSA bacteremia, presented with chief complaints of nausea, malaise and lethargy. Examination revealed a frail white male in moderate distress, regular heart rate and rhythm with a grade III/VI SEM at the LLSB radiating to the carotids. He was admitted with the presumptive diagnosis of uremic syndrome secondary to transplant failure on account of elevated BUN and CR and was scheduled for hemodialysis. In the dialysis unit, the patient developed acute onset chest pain with ST segment changes in V4-V6 and atrial fibrillation. Emergent treatment was initiated and he was transferred to the telemetry unit for monitoring. Subsequently, he developed recurrent episodes of pulmonary edema. Coronary angiography showed patent LIMA to LAD and emergent TEE was recommended prior to cardioversion, as atrial fibrillation was present for greater than 48 hours. The patient refused TEE, but allowed D-dimer estimation, if positive to be followed by TEE. D-dimer assay was positive (2000 ng/dL) and subsequent TEE revealed left atrial appendage clot, flailing of an aortic cusp with thickened leaflets and moderate aortic regurgitation. He also had MRSA bacteremia and was started on antibiotics with subsequent aortic valve replacement surgery. Postoperatively, patient improved clinically reverting to normal sinus rhythm He was discharged in a clinically stable condition. D-dimer is a product of intravascular clot lysis by the fibrinolytic system. An elevated level has a high sensitivity 2 for intravascular thrombus. This could be an effective tool for increasing operator efficiency during TEE for the exclusion of atrial clot prior to cardioversion. In this case the positive D-dimer also allowed TEE to be performed resulting in life saving valvular surgery. References: References : 1 Manning WJ, Weintraub RM, Waksmonski CA, et al . Accuracy of transesophageal echocardiography for identifying left atrial thrombi. A prospective, intraoperative study . Ann Intern Med 1995 ;123 :817 . 2 Ilkhanipour K, Wolfson AB, Walker H, et al . Combining clinical risk with D-dimer testing to rule out deep vein thrombosis . J Emerg Med 2004 ;27 :233 239